Structural Design and Transmission Performance Analysis of Double Modulated Coaxial Magnetic Gear - Peng Wu; Zina Zhu; Kaiyuan Li (Jixie chuandong)
Aiming at the problem of low transmission torque caused by the magnetic flux leakage phenomenon of the traditional magnetic gear permanent magnet，a coaxial magnetic gear model with double modulation structure is established based on the relative permeability derivation analysis of the permanent magnet air gap. The finite element method is used to simulate the model. The role of auxiliary flux modulation is analyzed and the flux density and transmission torque are calculated. The magnetic flux density and transmission torque of the conventional magnetic gear are compared. The simulation results show that the coaxial magnetic gear with double modulation structure can effectively enhance the air gap flux density，and reduce the magnetic flux leakage and increase the transmission torque. This double-modulated magnetic gear structure is of great significance for the research and application of the improvement of the torque density of the coaxial magnetic gear.